Improving The Food Safety in Constanta County: ANSVSA Controls, Results and Recommendations (2021) - Iuliana CONDULEȚ; Silvius STANCIU (Communications of International Proceedings, 2022)
This paper summarizes the official controls planned and carried out by the Sanitary Veterinary and Food Safety Directorate of Constanța in the year 2021 and it analyses the non-conformities encountered. According to the conducted research, it was observed that the number of controls planned at county level in the year 2021 was significantly lower than the number of controls carried out. The substantial difference between the number of planned control activities and those actually carried out is due to performing actions such as re-checks, import controls, service notes, or based on RASFF and AAC notifications. The number of inspections carried out in the commercial units on the Black Sea coast varies depending on several factors (tourist flows, tourist season, harvesting the agricultural production). The share of inspections is different for the four quarters of the year 2021. Prevention and recommendations are the main tools used by official inspectors in the field of food safety in Romania. The conducted research is part of the doctoral training stage and is the basis of a larger study on food safety in the South-Eastern Region of Romania.
Keywords: Nonconformities; Control; Food products; Constanța; Romania